Effect of Metallic Coating Thickness on Stainless Steel and Carbon Steel Welded Plate Using Eddy Current Testing - Ali K.; Mohamad A.J.; Othman A.A.Z.; Rifai D.; Salleh Z.; Siawpaw J.K.; Yaw C.T.; Tan J.D. (Institute of Physics, 2024)
Over the last few decades, steel has seen a sharp increase in utilisation. Non-destructive testing (NDT) methods still face difficulties when attempting to identify corrosion behind coatings. One of these difficulties is the lift-off that complex structures bring. Because of the structure's obstruction, corrosion goes undetected and can cause catastrophic breakdown. Additionally, lift-off effects lessen the sensitivity. On this paper the effect of coating thickness was measure by using metallic coating at carbon steel and stainless steel plates. The effect of coating thickness being identify based on measurement changes with different layer of coating thickness. From here the absolute and differential probe were used in measuring the lift-off because of coating thickness and the defect value. According on the result show that the Length of the crack at Toe, Root and Heat Affected Zone (HAZ) will reduce from 2.6% until 38.5% for carbon steel and 2.6% until 48.7% for stainless steel when the thickness of coating was increased. It different with Datum measurement where on carbon steel it increases from 0% until 11.5% and stainless steel 0.7% until 6%. Lastly the effect of coating thickness more effecting on defect measurement either carbon steel or stainless steel and artificial intelligent should be apply on each measurement for finding the right data getting in measurement as recommended. Published under licence by IOP Publishing Ltd.